Civilizational Dialogue in the Context of Late Nineteenth-Century Colonialism - Kumalasari, Ponco; Fauzan, Aris; Falikah, Tri Yaumil; Alaldaya, Rudyn Samaruddin (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2026)
This study examines models of civilizational dialogue articulated by Syed Ahmad Khan, Abdul Rahman al-Kawakibi, Shakib Arslan, and Wilfrid Scawen Blunt during the colonial era (1870–1920). Using a comparative historical approach, the research analyzes primary textual sources—including political essays, journalistic writings, literary works, and memoirs—supported by relevant secondary literature. Through thematic analysis and cross-textual comparison, the study identifies four interrelated dialogical frameworks: Khan's Dialogue of Accommodation, emphasizing Islamic–Western synthesis through education; al-Kawakibi's Dialogue of Resistance, which stresses political freedom as a prerequisite for genuine intercultural dialogue; Arslan's Dialogue of Revival, grounded in pan-Islamic solidarity; and Blunt's Dialogue of Empathy, shaped by imperial positionality and moral critique of empire. While previous studies have addressed these figures individually, this research fills a significant gap by offering a systematic comparative analysis of their dialogical visions within a shared colonial context. The findings reveal that, despite differing ideological and geographical backgrounds, all four thinkers advanced models of dialogue grounded in equality, mutual respect, and reciprocal learning, thereby challenging the hierarchical logic of colonial domination. This study contributes to civilizational dialogue theory by providing historically grounded and normatively relevant frameworks for intercultural engagement under conditions of power asymmetry.